The Use of Artificial Intelligence-Enabled Systems by Modern Armed Forces and Some Related Concerns - Prezelj, Iztok (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
Artificial intelligence (AI) is a new technology permeating several civilian and military aspects of human life. In the military and defence sectors, it is regarded as a game-changing technology that will affect the distribution of strategic power among major countries and improve efficiency at the tactical level by performing various specialised tasks. This paper tests and confirms the hypothesis that the emergence of AI introduces new possibilities to improve military and defence capabilities (benefits), alongside a broad range of concerns, challenges, and risks. This paper positions AI as a wave of revolution in military affairs, analyses a broad spectrum of potential and actual applications of AI by armed forces and defence establishments, and identifies several geopolitical and strategic concerns related to the development and use of AI systems. Based on these identified concerns, several regulatory approaches are proposed in the conclusion. Keywords: Artificial intelligence, autonomous weapon systems, intelligence, defence, geopolitics, challenges, revolution in military affairs (RMA), power struggle